The effect of corporate board attributes on bank stability - Karkowska, Renata (2020)
This study aims to empirically identify how a bank’s board structure (size, indepen- dence, and members’ affiliations) and quality (experience, background, and skills) affect its risk incentives. Specifically, it investigates whether banks’ solvency and corporate governance nexus changed after the 2007–2009 financial crisis. We employ a cross-country sample of 239 commercial and publicly traded banks covering 1997– 2016 and a panel regression for 40 countries. We acknowledge a negative relationship between board size and bank stability and demonstrate that an independent board may have constrained rather than encouraged risk in banks. The global financial crisis has not changed much in the corporate governance and stability of banks nexus. These findings are robust even while controlling for a range of alternative sensitivity estima- tions for bank stability. This result indicates that in the aftermath of the market meltdown, we still need to strengthen corporate governance practices which may mitigate the adverse effects of the crisis on the banking sector.